Peran Green Marketing dalam Membangun Brand Image dan Mendorong Keputusan Pembelian Produk di Rumah BUMN Kabanjahe - Melky Sedek Surbakti; Frans Antoni Sihite; Rayani Saragih; Benni Purba (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This study aims to analyze the role of green marketing in building brand image and encouraging purchasing decisions for products of MSMEs fostered by Rumah BUMN Kabanjahe. The background of this research is based on the increasing consumer awareness of environmental issues, which encourages business actors to implement environmentally friendly marketing strategies as a form of social responsibility and competitive advantage. This research employed a qualitative descriptive approach. Data were collected through in-depth interviews, observation, and documentation. The data were analyzed using data reduction, data display, and conclusion drawing techniques, supported by source, method, and time triangulation to ensure data validity.The results indicate that the implementation of green marketing at Rumah BUMN Kabanjahe is carried out through the use of environmentally friendly materials, simpler and reduced plastic packaging, consumer education regarding environmental awareness, and sustainability-based promotional strategies. These efforts contribute to the formation of a positive brand image as environmentally responsible and socially conscious products. A strong brand image subsequently influences both emotional and rational aspects of consumer purchasing decisions, leading to increased trust, loyalty, and buying interest in MSME products. Therefore, green marketing plays a significant role in strengthening brand image and promoting sustainable purchasing decisions. by Rumah BUMN Kabanjahe